Sex and Eating: Relationships Based on Wanting and Liking - Kang, Ying; Zheng, Lijun; Zheng, Yong (Frontiers in Psychology, 2016)
Sex and eating may have behavioral and psychological relationships and have cortical regions in common. This research investigated the general relationship between sex and eating from a reward perspective among the general population. Two-hundred and sixty-one Chinese participants were recruited via the internet (136 males, 125 females, mean age 30.46 years) to fill in questionnaires about wanting and liking for sex and eating. The results revealed that first, there was a positive correlation between wanting for sex and wanting to eat only for males. Second, the relationship between liking for sex and eating was also positive for males and not significant in females. Third, the correlation between sociosexual orientation and wanting to eat was significant only in females, and there was no significant correlation between sociosexual orientation and liking for eating. Fourth, emotional sex cravings (or emotional sexual activity) was positively correlated with emotional food cravings (or emotional eating behavior), with a higher magnitude correlation in males than females. Finally, analysis of wanting (liking) models of sex and eating for males and females revealed three models for wanting among females: high wanting, low wanting for eating, and low wanting for sex; and two models for wanting among males: high wanting and low wanting. Liking for sex and eating among females consisted of two types of model: high liking and low liking; whereas three type models existed for males: high liking for sex, high liking for eating, and low liking. In general, our research revealed that, as with other natural rewards, sex and eating have considerable commonality and are related in numerous ways.